Neuropsychological diagnostics: the rationale and experience of standardization and approbation of the «Ray test» and «Digital proof-reading» - L. I. Vasserman; N. I. Ananieva; M. V. Vasserman; R. V. Ezhova; B. B. Ershov; A. V. Chuikova; S. D. Tabulina (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
The article describes the authors’ point of view on the advisability of a wider use of the modern structural and functional approach in neuropsychological diagnostics, the need for multidimensional, complex studies combining traditional neuropsychological diagnostics with neurovisualization (MRT) technology that objectively identifies the morphofunctional specificity of brain deficiency with regard to functional interhemispheric asymmetry. In the qualification of the disorders of the VFF, a system of assessing the severity and dynamics of cognitive disorders is essential when analyzing its structural and content characteristics. Attention is drawn to the need for the development and wider application of standardized neuropsychological methods (tests) required in comparative studies and evaluation of their diagnostic effectiveness, taking into account the trends in the development of clinical neurosciences and the possibilities for neurorehabilitation, and the expansion of the capabilities of modern information technologies for creating a «bank» of psychodiagnostic information and Exchange of experience of specialists. As an example, the results of standardization and approbation of the methods «Complex figure of Ray-Osterritus» and «Digital proof-examination» on the clinical model of patients with temporal epilepsy are given.